2018
DOI: 10.15517/rbt.v66i1.33300
|View full text |Cite
|
Sign up to set email alerts
|

Cuando la conservación no puede seguir el ritmo del desarrollo: Estado de salud de los ecosistemas coralinos del Pacífico Norte de Costa Rica

Abstract: When conservation can keep up with development´s pace: Health status of coral ecosystems in the North Pacific of Costa Rica. Coral reefs are diverse and productive ecosystems, despite this, they are being threatened by human activities that enhance the detrimental impact of the natural phenomenon's like Harmful Algal Blooms (HAB). The north Pacific of Costa Rica has been characterized as one of the best regions for the coral reefs development in the country. However, many of these ecosystems are being lost as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 33 publications
4
19
0
7
Order By: Relevance
“…Biomass, trophic groups, and juvenile fishes: reef fish biomass at Cocos Island National Park (Costa Rica), a biodiversity hotspot highly protected from fishing, was estimated as 12.5 t ha -1 (Fourriére et al 2019), much higher than what we found (1.57 t ha -1 ). However, North Pacific Costa Rica has been subjected to habitat loss and intense fishing and fish biomass here is much lower (1.5 t ha -1 Alvarado et al, 2018) and similar to our findings. This suggest that Cabuyal and Zapotillal Bays, similarly to other areas in the region, (Villalobos-Rojas et al, 2014), have suffered impacts from fishing and habitat loss.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Biomass, trophic groups, and juvenile fishes: reef fish biomass at Cocos Island National Park (Costa Rica), a biodiversity hotspot highly protected from fishing, was estimated as 12.5 t ha -1 (Fourriére et al 2019), much higher than what we found (1.57 t ha -1 ). However, North Pacific Costa Rica has been subjected to habitat loss and intense fishing and fish biomass here is much lower (1.5 t ha -1 Alvarado et al, 2018) and similar to our findings. This suggest that Cabuyal and Zapotillal Bays, similarly to other areas in the region, (Villalobos-Rojas et al, 2014), have suffered impacts from fishing and habitat loss.…”
Section: Discussionsupporting
confidence: 90%
“…This leads to high densities of other herbivores such as the sea urchin D. mexicanum, which affects coral recruitment (Alvarado, Cortés, & Reyes-Bonilla, 2012). Thus, the low coral cover and high density of D. mexicanum that we found could be explained by a low biomass of herbivorous fish, similar to that reported by Alvarado et al (2018).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Between 2013 and 2017, a series of coral reefs health assessments in the Pacific of Costa Rica were conducted (Alvarado, Beita, Mena, Fernández-García, & Guzmán, 2015;Alvarado et al, 2016Alvarado et al, , 2018. These assessments focused solely on establishing the health status of these ecosystems, and here provides the baseline of their condition prior to the 2015-2016 global warming event.…”
Section: Methodsmentioning
confidence: 99%